PUBLIC-PRIVATE: Relasi Negara-Masyarakat dalam Tiga Cerita Rumah Tangga - Permatasari, Widya Ayu; Afiff, Suraya Abdulwahab (Studi Budaya Nusantara, 2019)
The establishment of a gold mining company in Desa S caused the split of society into two part. The first part of the community supported mining companies and the second part, some of them refused the establishment of mining companies. So far, the phenomenon of the split of society into two part, often seen in the national and local domains. Whereas, this study wants to see this phenomenon occur in the realm of the household. The division of society in the realm of households is interesting to understand when the role of local state actors is in it. This condition occurred in my research, where there were three households in which there were local level state actors. The position of these state actors is quite dilemma, on the one hand, a family member supports a mining company, on the other hand, one family member rejects a mining company. The study of state-society relations is an appropriate study in understanding these conditions. In this study, the approach used in assessing the relation of state-society is Migdal's "state in society". One of Migdal's main arguments in this approach is that the state works on two levels, practice and image, where Migdal presupposes an entity to have a social boundary between the public (state and agency) and private (subject to state rules). However, what happened in the research that I did, there was no separation between public and private in the state-society relations in the household domain. Therefore, this study would like to show that the boundary between public and private is blended and overlaps each other in the relations of the state-society in the household domain.